IL6 gene polymorphism association with calcific aortic valve stenosis and influence on serum levels of interleukin-6 - Junco-Vicente, Alejandro; Solache-Berrocal, Guillermo; del Río-García, Álvaro; Rolle-Sóñora, Valeria; Areces, Sheila; Morís, César; Martín, María; Rodríguez, Isabel (Frontiers in Cardiovascular Medicine, 2022)
Aortic valve stenosis is the most frequent valve disease in developed countries and its prevalence will increase with population aging. There is still no pharmaceutical treatment nor biomarker to determine the susceptibility to develop aortic stenosis. Therefore, we analyzed the association of polymorphisms in risk loci with calcific aortic stenosis. Patients with aortic valve disease were genotyped for PALMD rs6702619, LPA rs10455872, and IL6 rs1800795 polymorphisms and circulating levels of interleukin-6 (IL-6) were measured. Calcium content of leaflets obtained in valve replacement surgeries was determined by micro-computed tomography. In the genotyping of 578 individuals, we found significant association between PALMD and IL6 polymorphisms and aortic stenosis in patients with tricuspid aortic valve, independently of other potentially confounding variables such as age and dyslipidemia. There was no association of these polymorphisms with valve calcium content, but this value correlated with the mean aortic pressure gradient (r= 0.44; P< 0.001). The CC genotype of IL6 polymorphism was associated with higher levels of serum IL-6 compared to other genotypes (23.5 pg/ml vs. 10.5 pg/ml, respectively; P= 0.029). Therefore, patients carrying the CC genotype of IL6 rs1800795 polymorphism present higher levels of circulating IL-6 and this could contribute to the severity of the aortic valve stenosis. Our results agree with the identification of IL6 as a locus risk for stenosis and also with the intervention of this cytokine in aortic valve calcification. A more exhaustive follow-up of those patients carrying risk genotypes is therefore recommended.